2014
DOI: 10.1186/1471-2180-14-130
|View full text |Cite
|
Sign up to set email alerts
|

Polymicrobial airway bacterial communities in adult bronchiectasis patients

Abstract: BackgroundChronic airway infection contributes to the underlying pathogenesis of non-cystic fibrosis bronchiectasis (NCFBr). In contrast to other chronic airway infections, associated with COPD and CF bronchiectasis, where polymicrobial communities have been implicated in lung damage due to the vicious circle of recurrent bacterial infections and inflammation, there is sparse information on the composition of bacterial communities in NCFBr. Seventy consecutive patients were recruited from an outpatient adult N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 38 publications
(62 reference statements)
1
51
0
Order By: Relevance
“…In contrast, another study reported no correlation between clinical parameters and microbiota, with bacterial load and composition unchanged by antibiotic treatment of exacerbations . Based on culture and pyrosequencing of sputum from adults with bronchiectasis, another study found the exacerbation frequency and episodes of clinical stability were associated in some patients with significantly different bacterial community structures . However, this study was cross‐sectional and suffered from limited resolution provided by pyrosequencing where individual species cannot be identified.…”
Section: Etiology and Pathogenesismentioning
confidence: 86%
See 1 more Smart Citation
“…In contrast, another study reported no correlation between clinical parameters and microbiota, with bacterial load and composition unchanged by antibiotic treatment of exacerbations . Based on culture and pyrosequencing of sputum from adults with bronchiectasis, another study found the exacerbation frequency and episodes of clinical stability were associated in some patients with significantly different bacterial community structures . However, this study was cross‐sectional and suffered from limited resolution provided by pyrosequencing where individual species cannot be identified.…”
Section: Etiology and Pathogenesismentioning
confidence: 86%
“…Three adult‐based studies highlighted the abundance of anaerobic bacteria and the complex microbiota within the lungs of bronchiectasis patients . Bacterial community composition positively correlated with forced expiratory volume in 1 sec (FEV 1 ), neutrophil count and cough score .…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
“…Other bacterial genera described in bronchiectasis airways include Streptococcus, Prevotella, Veillonella and Staphylococcus [65][66][67]. P. aeruginosa is associated with poorer pulmonary function, higher hospitalisation rates and greater morbidity and mortality compared to H. influenzae [68][69][70][71][72][73][74][75][76][77][78].…”
Section: Geographic Variation In the Microbiology Of Bronchiectasis Tmentioning
confidence: 99%
“…Haemophilus influenzae and P. aeruginosa are the most commonly isolated organisms in several European studies using aerobic selective cultures, although no organisms are isolated in 23-27% of patients [9,17,36,37]. New methods to study lung microbiota have found that the diversity of airway infection is underestimated, with anaerobic bacteria found in up to 83% of sputum samples, and that three taxa, Streptococcaceae, Pseudomonadaceae and Pasturellaceae, seem to be dominant [38].…”
Section: Consensus Statementmentioning
confidence: 99%